Corporate recovery in Brazil: characteristics, improvements, limits - Pimenta, Eduardo Goulart (2006)
THE CENTRAL PURPOSE OF THIS STUDY IS TO EXAMINE SOME QUESTIONS ABOUT THE INSTITUTE OF CORPORATE RECOVERY, RECENTLY INCORPORATED IN OUR LEGAL SYSTEM BY THE LAW 11.101/2005. THE INTENTION IS TO PRESENT ITS CHARACTERS, OBJECTIVES AND TO DISCUSS HOW IT CAN BE EFFECTIVE FACING THE ECONOMIC CIRCUMSTANCES THAT MADE FAIL THE PRECEDING LEGISLATION. AS SUBSIDIES THE TEXT DISCUSS THE DIFFERENCE IN PHASE BETWEEN THE ANTERIOR LAW (DECRETO-LEI 7.661/1945) AND THE MODERN PRINCIPLES OF BANKRUPTCY LAW, AS WELL AS THE TRY TO INCORPORATE THEM IN THE TEXT OF LAW 11.101/2005. IN OTHER SIDE, THIS STUDY APPOINT AND COMMENT SOME OF THE MOST IMPORTANT INNOVATIONS OF THE NEW BRAZILIAN BANKRUPTCY LAW, SPECIALLY THE ADVANCES FOR THE RAPID AND JOUST LIQUIDATION OF THE BROKEN ENTERPRISES OR ITS FORTUITOUS RECOVERY AND MAINTENANCE.